Issues of Electricity Supply in the Water Industry Teaching Methodology - Olimovich, Mirzayev (Physical Sciences, Life Science and Engineering, 2024)
This article examines the methods used to educate energy supply difficulties in the water and agricultural industries, discusses new energy supply innovation technologies, and offers suggestions based on a comparison of domestic and international experience.